2009
DOI: 10.1016/j.autneu.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic tonic dilatory influences on cerebral vessels

Abstract: Parasympathetic nerves from the pterygopalatine ganglia may participate in development of cluster headaches, in vascular responses to hypertension and in modulation of damage due to stroke. Stimulation of the nerves elicits cerebral vasodilatation, but it is not known if the nerves tonically influence cerebrovascular tone. We hypothesized that parasympathetics provide a tonic vasodilator influence and tested that hypothesis by measuring cerebral blood flow in anesthetized rats before and after removal of a pte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Recently, Gourine et al reported that RIPC might be associated with the nerve reflex, which is the sensory afferent pathway from the peripheral organ (limbs) and parasympathetic vagal efferent outflow to the heart in rats [20]. Previous studies showed that there is evidence of parasympathetic vasodilator in the masseter muscle [21], lower lip [22] and brain vessels [23] in animals. Those findings indicated that vasodilatation is a result of reflex via increasing parasympathetic activity.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Gourine et al reported that RIPC might be associated with the nerve reflex, which is the sensory afferent pathway from the peripheral organ (limbs) and parasympathetic vagal efferent outflow to the heart in rats [20]. Previous studies showed that there is evidence of parasympathetic vasodilator in the masseter muscle [21], lower lip [22] and brain vessels [23] in animals. Those findings indicated that vasodilatation is a result of reflex via increasing parasympathetic activity.…”
Section: Discussionmentioning
confidence: 98%
“…Like the sympathetic arm, parasympathetic innervation also displays tonic influence on the cerebrovasculature, but instead acts as a potent vasodilator (50,61,118). However, beyond its tonic role, and importance in certain pathologies [e.g., Alzheimer's (161)], the active parasympathetic contribution to physiological perturbations remains less understood.…”
Section: Neurogenic Regulation Of Cerebral Blood Flowmentioning
confidence: 98%
“…This lack of effect is consistent with previous work using this same microinjection technique in which we demonstrated that placements as little as 500 μm away from the RVM had no effect on nocifensor reflexes (Heinricher and Kaplan, 1991; Heinricher et al, 1994). These anatomical controls thus allow us to localize drug action to the RVM (Yaksh and Rudy, 1978; Wise and Hoffman, 1992), and rule out diffusion to brainstem sympathetic and parasympathetic premotor areas previously implicated in regulation of cerebral blood flow, such as the superior salivatory nuclei or rostral ventrolateral medulla (Underwood et al, 1992; Golanov and Reis, 1994; Talman et al, 2007; Boysen et al, 2009). …”
Section: Discussionmentioning
confidence: 99%